1984
DOI: 10.1088/0022-3719/17/35/020
|View full text |Cite
|
Sign up to set email alerts
|

Optical studies of the structure of porous silicon films formed in p-type degenerate and non-degenerate silicon

Abstract: The detailed structure of porous Si (PS) layers formed in p-type wafers with resistivities 0.01-25 Omega cm has been investigated using reflectance, transmission, ellipsometry and photoluminescence techniques. Marked differences were observed in the optical properties of PS formed in degenerate or non-degenerate Si and these results are correlated with the results of other techniques. The optical techniques together with effective medium modelling have been shown to be useful non-destructive methods for either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
1
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(95 citation statements)
references
References 18 publications
6
85
1
3
Order By: Relevance
“…The silicon on sapphire technology (SOS), and silicidation of porous silicon were reported by Ito et al in 1989(Ito et al, 1989. In 1984 Pickering et al (Pickering et al, 1984) have observed the low temperature photoluminescence in PS. But the discovery of room-temperature photo-and electroluminescence by L. Canham in 1990 boosted the research on porous silicon because of the huge potential in silicon-based integrated sensing and photonic devices (Canham, 1990(Canham, , 1997b(Canham, , 1997c(Canham, ,1997dCanham et al,1991).…”
Section: Applications Of Porous Siliconmentioning
confidence: 99%
“…The silicon on sapphire technology (SOS), and silicidation of porous silicon were reported by Ito et al in 1989(Ito et al, 1989. In 1984 Pickering et al (Pickering et al, 1984) have observed the low temperature photoluminescence in PS. But the discovery of room-temperature photo-and electroluminescence by L. Canham in 1990 boosted the research on porous silicon because of the huge potential in silicon-based integrated sensing and photonic devices (Canham, 1990(Canham, , 1997b(Canham, , 1997c(Canham, ,1997dCanham et al,1991).…”
Section: Applications Of Porous Siliconmentioning
confidence: 99%
“…2,3 In the 1980's, several studies of the optical properties of PSi were published and photoluminescence ͑PL͒ in the deep red/near infrared was detected at cryogenic temperatures. 4 The roomtemperature luminescence, which has been observed from PSi usually formed in a concentrated HF based electrolyte by Canham 5 in 1990, has attracted considerable attention because of its potential use in the development of silicon-based optoelectronic devices, 6 such as electroluminescent displays 7 and photodetector. 8 The porous structure and a relatively large surface area have also made the silicon an ideal matrix for immobilization of a variety of biomolecules including enzymes, 9 DNA fragments, 10 and antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, the dielectric response of a porous Si (p-Si) is described by the effective medium approximations [9,10], that simply average the dielectric contribution from the air pores and the backbones of the silicon (nano-Si). The dielectrics of a nano-Si is often presumed to take the bulk constant and the ε nano-Si can be derived from the measured ε eff of a p-Si by using the simple Looygenga formula [11]: …”
Section: Introductionmentioning
confidence: 99%